Results of peripheral vascular surgery in the "F" Surgical Clinic, years 1979-1984 - Matteucci, Pablo; Tchekmedjian, Vartan; Lucinschi, Alicia (Cirugía del Uruguay, 1986)
Authors present results obtained in a series of 184 operations in peripheríc vascular surgery, with an 83% distant follow up. Figures are given in detail, noticeable is mortality at hospital 7,4%, with 7% amputations in the first 30 days.